Office blood pressure and obesity in children with X-linked hypophosphatemia - Böckmann, Ineke; Leifheit-Nestler, Maren; Rehberg, Mirko; Spartà, Giuseppina; Evers, Katrina; Schlingmann, Karl Peter; Kemper, Markus J.; Richter-Unruh, Annette; Hiort, Olaf; Grohmann-Held, Karina; Derichs, Ute; Freiberg, Clemens; et al. (Calcified tissue international, 2025)
X-linked hypophosphatemia (XLH) is the most common inherited form of hypophosphatemic rickets. Children with XLH have an increased risk of obesity, which may promote high blood pressure, but data on blood pressure in XLH are inconclusive. We aimed to assess blood pressure and its determinants in pediatric XLH patients. We conduct a prospective, multicenter observational study of children with XLH in Germany and Switzerland. Office blood pressure and body mass index (BMI) were annually measured in 128 pediatric XLH patients with a median follow-up of 2 years (range 1-6). Potential predictors of blood pressure were investigated by Spearman correlation. Seventeen percent of patients were treated with phosphate supplements and active vitamin D for a median of 8 years, 83% of patients received burosumab for 2.3 years with 3.1 years of prior treatment with phosphate supplements and active vitamin D. Median systolic (0.75 z-score) and diastolic (0.32 z-score) blood pressure and BMI (0.72 z-score) were increased compared to healthy children (each p < 0.01). The prevalence of obesity (9.8% vs. 3%), arterial hypertension (26.2% vs. 5%), and high-normal blood pressure (22.9% vs. 5%) was higher in the XLH cohort compared to the general pediatric population (each p < 0.001). Spearman rank correlation analysis revealed significant associations between both systolic (r = 0.24; p < 0.01) and diastolic (r = 0.20; p < 0.05) blood pressure with BMI, while the mode of treatment, i.e. burosumab versus phosphate supplements and active vitamin D, was no significant correlate. Children with XLH present with elevated office blood pressure values, associated with elevated BMI.
Online veröffentlicht: 28. März 2025
Gesehen am 14.11.2025